2009
DOI: 10.1097/mpa.0b013e3181a85999
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antitumor Effect of Combined Gemcitabine and Proton Radiation in the Treatment of Pancreatic Cancer

Abstract: OBJECTIVES-This study evaluates the efficacy of combining proton irradiation with gemcitabine and the role the inhibitor of apoptosis proteins (IAP) survivin & XIAP play in the radiosensitive vs. radioresistant status of pancreatic cancer. METHODS-The radioresistant (PANC-1) and radiosensitive (MIA PaCa-2) pancreatic carcinoma cells response to combined gemcitabine and proton irradiation was compared. Cells were treated with 0.1 -500 μ-M gemcitabine and 0 -15 Gy proton irradiation after which Trypan blue and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 36 publications
(41 reference statements)
0
26
0
Order By: Relevance
“…Conversely, inhibition of Survivin reduces tumor growth potential and sensitizes tumor cells to chemotherapeutic agents, such as paclitaxel, cisplatin, etoposide, gamma irradiation, and immunotherapy [48]. More recently, we have investigated Survivin’s role in resistance to proton irradiation of pancreatic cancer cells and found that stress proteins such as Survivin and the X-linked inhibitor of apoptosis (XIAP) protein play important roles in resistance to proton-based treatment options [49]. We therefore investigated whether stress, delivered by proton irradiation to HeLaS/POZnSurvivin cells, stimulated enhanced Survivin release to the extracellular conditioned medium compared with control conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, inhibition of Survivin reduces tumor growth potential and sensitizes tumor cells to chemotherapeutic agents, such as paclitaxel, cisplatin, etoposide, gamma irradiation, and immunotherapy [48]. More recently, we have investigated Survivin’s role in resistance to proton irradiation of pancreatic cancer cells and found that stress proteins such as Survivin and the X-linked inhibitor of apoptosis (XIAP) protein play important roles in resistance to proton-based treatment options [49]. We therefore investigated whether stress, delivered by proton irradiation to HeLaS/POZnSurvivin cells, stimulated enhanced Survivin release to the extracellular conditioned medium compared with control conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, NF-kB activity and IAP expression have been implicated in resistance to Gemcitabine (69-70). Gemcitabine induces an increase in IAP expression in pancreatic cancer cells, particularly Survivin and XIAP, as well as cIAP1 in lung cancer cells (71-74). …”
Section: Discussionmentioning
confidence: 99%
“…This can be due to a decrease in levels of endogenous IAP inhibitors, abnormalities in the gene, or an increase in the expression of either mRNA or protein 40. Specifically, the high levels of survivin expression in cancer cells have been associated with dismal prognosis, disease progression, metastatic dissemination, chemo- and radiotherapy resistance, and overall dismal disease outcome 28,41,42. In many cancer types, such as glioblastoma, renal cell carcinoma, and liver and pancreatic cancer, the chromosome region of 11q21–23, which includes both the cIAP1 and cIAP2 genes, is shown to be amplified in these diseases, making cIAP1/2 protooncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous efforts have been made to target these IAPs to address the problem with resistance to therapy. XIAP silencing by siRNA in pancreatic cancer cell lines has been shown to increase Gem sensitivity,45 as well as an enhancement of cell death when treated with both Gem and proton radiation 42. Other studies have targeted survivin, showing that knocking this IAP down with siRNA caused Gem chemosensitivity 46.…”
Section: Discussionmentioning
confidence: 99%